Public awareness of acute myocardial infarction symptoms and emergency response in community residents. (14th October 2021) - Ma, J; Zhang, N; Xiao, J.-Y; Wang, J.-X; Li, X.-W; Wang, J; Zhang, Y; Zheng, Q.-X; Zhao, S.-Y; Han, P; Yang, Y.-N; Gao, M.-D; et al.
Abstract: Background: Patient delay in seeking help has been reported to be a major factor that related to delay in care of acute myocardial infarction (AMI). Lack the knowledge of symptoms may translate to behavioral deficiencies which lead up to failing to seek medical assistant at early stage of AMI. Purpose: The aim of present study is to investigate the awareness of AMI symptoms and the emergency responses among community residents over 35 years old. Methods: The sample was proportionally distributed by age according to the national census data. The sex ratio was 1:1. The sample size is calculated according to the significance level of 0.05, the allowable error of 0.1, and the estimated Excellent awareness level of 10%. The final sample size is adjusted to 4200, considering non-response rate of 20%. Multi-stage stratified random sampling was used. On the first stage, two districts each in urban and rural regions were randomly selected. On the second stage, 3–10 community health service centers were randomly selected in each district. On the third stage, residents over 35 managed by the community health service center were proportionally sampled to be interviewed. A structured questionnaire was used and the survey was conducted in a face-to-face interview by clinical physicians. Logistic regression was applied to analyze factors related to Good knowledge. Results: The top three symptom recognized by public is "pain or discomfort in the chest" (71.3%), followed by "difficulty breathing" (65.1%) and "pain or discomfort in the jaw, neck, or back" (60.9%). 85.0% chose to call an ambulance as first response when witness others having an AMI. Those who lives alone (OR=1.408; 95% CI, 1.005–1.972) and whose immediate family had been diagnosed with AMI (OR=1.510; 95% CI, 1.040–2.192) has better knowledge. A significant positive correlation was observed for those with hypertension (OR=1.199; 95% CI, 1.007–1.429), while a negative correlation was observed for those with diabetes (OR=0.788; 95% CI, 0.626–0.992). Public education could improve Good knowledge (OR=1.662; 95% CI, 1.388–1.990), while doctoral advise has been shown negative impact (OR=0.824; 95% CI, 0.691–0.984). Conclusions: Our data provide first population-based estimates of public awareness in our country. Further promotional strategies to increase overall awareness in general public are seriously needed. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Major Science and Technology Projects of Tianjin Science and Technology Commission